Suicidal ideation and behavior in youth in low- and middle-income countries: A brief review of risk factors and implications for prevention - Renaud, Johanne; MacNeil, Sasha Leigh; Vijayakumar, Lakshmi; Spodenkiewicz, Michel; Daniels, Sylvanne; Brent, David A.; Turecki, Gustavo (Frontiers in Psychiatry, 2022)
Although global rates of suicide have dropped in the last 30 years, youth in low- and middle-income countries (LMICs) continue to be highly represented in suicide statistics yet underrepresented in research. In this review we present the epidemiology of suicide, suicidal ideation, and suicide attempts among youth in LMICs. We also describe population-level (attitudes towards suicide, socioeconomic, and societal factors) and individual-level clinical and psychosocial risk factors, highlighting specific considerations pertaining to youth in LMICs. These specific considerations in risk factors within this population can inform how multi-level prevention strategies may be targeted to meet their specific needs. Prevention and intervention strategies relying on the stepped-care framework focusing on population-, community-, and individual level targets while considering locally- and culturally relevant practices are key in LMICs. In addition, systemic approaches favoring school-based and family-based interventions are important among youth. Cross-culturally adapted multimodal prevention strategies targeting the heterogeneity that exists in healthcare systems, suicide rates, and risk factors in these countries should be accorded a high priority to reduce the burden of suicide among youth in LMICs.